FVC, FEV1, FEV1/FVC ratio and FEF25-75% in End-stage renal disease (ESRD) patients undergoing maintenance haemodialysis - Hoque, Farhana; Begum, Shelina; Latif, Abdul; Begum, Afroza; Sultana, Shamima (Journal of Bangladesh Society of Physiologist, 2013)
Background: End-stage renal disease causes multiple pulmonary complications and lung functions are decreased in ESRD patients undergoing maintenance haemodialysis. Objectives: To observe FVC, FEV1, FEV1/FVC ratio and FEF25-75% in ESRD patients undergoing maintenance haemodialysis to evaluate their lung functions status. Methods: This cross sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, from July 2011 to June 2012. For this, 30 ESRD patients aged 25-55 years undergoing maintenance haemodialysis with less than 1 year duration were studied and 30 age, sex matched healthy subjects were taken as control. Patients were selected from the Nephrology department of BSMMU, Dhaka. FVC, FEV1, FEV1/FVC ratio and FEF25-75% were measured by a Digital Spirometer. For statistical analysis Independent Samplet test and One way ANOVA test were performed as applicable. Results: The mean percentage of predicted values of FVC, FEV1 and FEF25-75% were significantly lower in patients except FEV1/FVC ratio which was almost similar to control. 63.33% patients had restrictive and 36.67% patients had both restrictive and obstructive (small airway obstruction) feature. Conclusion: This study concluded that some pulmonary functions were markedly reduced in ESRD patients undergoing maintenance haemodialysis. In addition most of the patients were suffering from restrictive and some of them were affected with both obstructive and restrictive type of pulmonary disorders. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16645 J Bangladesh Soc Physiol. 2013, June; 8(1): 33-36